Sincronia entre catalases e peroxidades de ascorbato na proteção contra danos oxidativos em folhas de feijão caupi expostas aos estresses hídrico e salino - Lima, João Paulo Matos Santos (2007)
Water stress, induced by drought or salinity, is the major environmental restriction to plant survive and crop sustainability, specially in semi-arid areas, where they are often associated to high temperatures and high radiation rates [...]